Broadcasting Family Law Information to the Public to Achieve Transparency in the Press Suluhnews, Banten - Dusman Samsudin; Reza Fahlevi Nurpaiz (International Research and Development for Human Beings (IRDH), 2025)
Broadcasting is the activity of disseminating content in the form of information, entertainment, and education to the general public through various channels such as radio, television, and digital media. The aim of this research and community service is to implement the broadcasting of family law information to the public in order to realise press transparency in Suluhnews, Banten. Research and community service activities are conducted in three forms, including discussions and networking with stakeholders about the importance of broadcasting legal information and press transparency, discussions and networking with the general public about the importance of broadcasting legal information and press transparency, and training students in news writing about family law. The results obtained include 7 (seven) points, namely the creation of family legal literacy activities in the community, the formation of a Collaborative Model between Local Media and Academics, studying Ways to Improve the Quality of Legal-Based Journalistic Content, community participation, strengthening the role of media as agents of transparency and education, and training school students to become young journalists, and Policy Recommendations for Local Government and Media Institutions. Suggestions that can be provided to the general public include the need for training in news writing that involves collaboration from various stakeholders